Síntese e caracterização de heteropentâmeros formados por cobaltoftalocianina e cobaltotetrafenilporfirina - Martins, Tássia Joi (Universidade Federal de São Carlos, 2012)
Metalloporphyrins and metalophthalocyanines assemblies have attracted in the last few decades. The syntheses of face to face systems containing porphyrins or phthalocyanines can found in literature, however few works reported these arrangements in mixed systems. A new system composed by cobaltophthalocyanine (CoPc) and cobaltotetraphenylporphyrin (CoTPP) assembled in a face to face arrangement by using a rigid and conjugate ligand, like pyrazine (pyz), may result in a new material with interesting properties. Recently, in our laboratory, a new synthetic route for mixed complexes like CoPc(pyz)CoTPP(pyz)CoPc and CoTPP(pyz)CoPc(pyz)CoTPP was developed. Nevertheless, the possibility of an increase in the chain has not been investigated. This work aimed the investigation of a synthesis of heteropentamers formed by metaloporphyrins and metalophthalocyanines complexes, relating their properties with precursor s complexes. The heteropentamers synthesis was carried out using the same methodology described for heterotriads. It was synthesized the follow sequences of heteropentamers: CoPc(pyz)CoTPP(pyz)CoPc(pyz)CoTPP(pyz)CoPc 2, CoTPP(pyz)CoPc(pyz)CoTPP(pyz)CoPc(pyz)CoTPP 1 and 2. For each synthesis, two fractions were obtained and isolated. The characterization was carried out by vibrational spectroscopy, Uv-vis spectroscopy, thermal analyses and solubility tests. The vibrational spectra showed the coordination of the macrocycles to the pyrazine terminal ligands on the adducts. This was also observed by thermogravimetry analysis. By the thermal analysis was also possible to verify differences in binding between the terminal pyrazines and the internal pyrazine ligands. The electronic spectra of heteropentamers showed chacacteristic bands of each macrocycle, however were observed shifts in the absorption bands of phthalocyanines and porphyrins in the heteropentamers fractions.
Keywords: Química inorgânica; Metaloftalocianina; Metaloporfirinas; Complexos mistos; Propriedades eletrônicas; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA